Trust Radius versus Trust Level: Radius of Trust as a Distinct Trust Construct. (December 2014) - van Hoorn, André
In their October 2011 ASR article, "How General Is Trust in 'Most People'? Solving the Radius of Trust Problem, " Delhey, Newton, and Welzel pioneer the measurement of trust radius, defined as the width of the circle of people among whom a certain trust level exists. One key finding of their study is that trust radius correlates so strongly with out-group trust level that the two are essentially identical constructs; this clashes with standard theory's finding that trust level and trust radius are distinct trust constructs. This result proves to be erroneous, however, due to a mistaken label. I seek to correct this labeling error and find that trust radius is, in fact, a separate trust construct. Trust radius differs from established trust level constructs such as level of trust in most people and level of out-group trust, not only theoretically but empirically as well.